Econometric analysis of disseminating sustainable intensification practices: evidence from Ghana - Bedi, S.M. (Rheinischen Friedrich-Wilhelms-Universitat, 2021)
Adoption of sustainable intensification (SI) of agricultural practices is essential for increasing food production in more sustainable way. Dis-adoption of agricultural technologies is pervasive among smallholder farmers in sub-Saharan Africa after withdrawal of most programme interventions. Based on data collected from 700 farm households of an agricultural research for development programme in northern Ghana. This study i) examines alternative ways of inducing farmers into adopting new agricultural technologies, ii) determines the marginal farm household entrants that must be targeted during scaling-up and-out SI practices, and iii) identify the farm households that benefited most from SI adoption during diffusion. Myriads of econometric methods that account for sample selection bias were used while addressing the objectives of the study. The empirical results show that inducing farmers to adopt SI practices resulted in an increase in maize yield and net income of farmers. Results also suggest that the continuous inducement of farmers led to positive and significant increase in maize yield and net income of induced farmers. Point estimates reveal that stopping the inducement could have led to a decrease in maize yield and net income of induced farmers. The findings also indicate that farmers’ resource endowment and unobserved factors influence the marginal benefits of adopting SI practices, and that scalingup SI practices will favour marginal farm household entrants associated with the least probability of adoption based on observed socioeconomics characteristics. Finally, the results show that the adopters that benefited most from adoption based on the net income of maize and legume yield during SI diffusion are much more likely to live in highly resource endowed farm households with relatively younger household heads and fewer household members. In addition, they are much more likely to travel longer distances before reaching the nearest weekly market and motorable road. Overall, the study provides empirical evidence that the adoption of SI practices enhances farm performance and household welfare, and that scaling-up should be targeted. The study also suggests that the provision of support services is a necessary condition for sustaining adoption and thus collaboration between programme interventions with key government ministries and private business mechanisation firms are needed in the scaling-up policy decision making.